Pengembangan UMKM dengan Inovasi Pengemasan dan Kemitraan di Desa Tamansari, Bogor - Wirahadi, Syahrul; Sari, Khairina; Ramadhani, Hanif Fadila; Jesika, Reni; Nugroho, Teresa Maria Judith Trianadewi; Gifari, Muhammad Luthfi Al; Wafa, Yasmin Azimah; Ismail, Muhammad; Alifa, Naila Nur; Kartika, Lindawati (Jurnal Pusat Inovasi Masyarakat, 2024)
Tamansari Village in Bogor Regency boasts a key commodity in pohpohan leaves, which has significant potential to be developed by Micro, Small, and Medium Enterprises (UMKM) into processed products such as chips through packaging innovation and partnership strategies. The UMKM "CLB Raos," which has been producing pohpohan chips since 1998, faces key challenges in marketing due to unappealing packaging and a limited partnership network, causing the business to temporarily halt. This mentoring program aims to enhance the competitiveness and sustainability of pohpohan chips through strategic planning, social approaches, implementation, and evaluation. The main interventions in this program include improving packaging from simple clear plastic to full-print aluminum foil, rebranding the product to "KEPOTA," and registering the business with a Business Identification Number (NIB) and Halal Certification. Partnerships with the "Sobat Tani IPB" cafe and the entrepreneurship extracurricular program at SMA N 1 Tamansari were also established to broaden the market reach. The results show a significant increase in the product's appeal and competitiveness in the market. The main challenge faced by this micro-enterprise is the limited mobility of the UMKM actors, which hinders independent product distribution. Therefore, packaging innovation and strategic partnerships are crucial for UMKM development, especially in expanding market reach.